SECONDARY GLAUCOMA AFTER VITREORETINAL SURGERY: A RETROSPECTIVE OBSERVASIONAL STUDY: Oral Presentation - Observational Study - Resident - Gunawan, Liani Mulasari; Rifada, R. Maula; Gustianty, Elsa; Umbara, Sonie (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesSecondary glaucoma is the most common complication after vitreoretinal surgery. Pars PlanaVitrectomy (PPV) is a common surgical procedure aimed at removing vitreous gel and replacing itwith variety of substances denominated tamponades. Vitreous removal and replacement may causeincreased intraocular pressure (IOP). The IOP can be reduced with medical treatment or surgery.The purpose of this study is to describe the characteristics of secondary glaucoma after vitreoretinalsurgery in National Eye Center Cicendo Hospital from January 2019 - December 2020. MethodsThis study was a retrospective descriptive study which data were obtained from medical records.Data such as age, gender, vitrectomy tamponades, IOP, onset of glaucoma, and glaucoma treatmentwere collected. ResultsOne hundred fifty-three eyes were referred to Glaucoma Unit with increasing IOP after vitreoretinalsurgery. PPV with tamponade was done in 141 eyes (92.16%) and silicone oil (SO) 1000 centistokes(cSt) was the most used tamponade in 101 eyes (66.07%). Secondary glaucoma with open angle wasthe most common type in 124 eyes (81.04%). Secondary glaucoma developed in 4-7 weeks aftersurgery, with the highest IOP recorded at 31-40 mmHg. The IOP decreased after SO evacuation withinitial glaucoma treatment in 121 eyes (79.09%), and glaucoma surgery was performed in 32 eyes(20.91%). ConclusionSilicon oil as a tamponade agent after PPV may cause rise IOP in the post-operative period.Evacuation SO needs to be done after retinal adhesion to prevent secondary glaucoma. Therefore,timely detection and anti-glaucoma treatment are important to decreased IOP, or filtration surgerycan be performed.